THE RIGHT TO EXIST OF TRANSGENDER ATHLETES IN THE SCOPE SPORT IN THE LIGHT OF THE CONSTITUTIONAL PRINCIPLE OF EQUALITY (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
The research deals with the permanence of the marginalization of transgender athletes and the removal of the constitutional guarantee of equality expressed in art. 5, items I and XXVIII of the Federal Constitution, which provides for the security of all men and women in the free participation of sporting activities. The present work addresses that the inclusion of transgender athletes in the gender sports categories with which they identify is still a controversial issue due to the conflict between principles of law, the retrograde thinking of society, a rigid work and legislative conservative. Sports law faces challenges when it comes to public policies (and their absence) and effective legal norms for transgenders, thus resulting in the perpetuation of inequalities and the exclusion of transgender athletes in sports. Furthermore, the current and persistent discriminatory Brazilian scenario is exposed, especially due to the various bills that are being processed by the legislative houses in an attempt to validate the determination of biological sex as the only determinant of high-performance sports categories. The present study also addresses that the existing generic norms and the performance of the Federal Supreme Court (through contentious jurisdiction) are unable to derive an inclusive sporting right and non-discrimination based on gender identification, sometimes assumptions of a safe and welcoming environment for everyone. Furthermore, it explores that the principles established by the International Olympic Committee are not with the Principle of the Dignity of the Human Person, with no effectiveness in its guidelines for the transgender population. The methodology used in this work is based on a bibliographic review of contemporary authors related to the theme, also including journalistic reports, scientific articles published in magazines and periodicals in line with MEC guidelines, repositories of dissertations and theses, in addition, of course, to to use deductive methods, case studies and jurisprudential analysis on the exposed reflection.